CHARACTERISTICS OF THE PROSECUTOR'S AUTHORITIES DURING THE SUSPENSION OF THE INVESTIGATION (Bulletin of criminological association of Ukraine, 2024)
The nature of the powers of the prosecutor during the suspension of the investigation due to his functional purpose in criminal proceedings was investigated, and his list was provided. On the basis of their analysis, it was established that they mostly relate to the implementation of the function of procedural management, which consists in the supervision of compliance with the law by the inquirer when deciding the question of stopping and resuming the inquiry, observing the rights and interests of the suspect, the victim and other participants in the criminal proceedings whose rights and interests are affected by the adoption such procedural decisions. The author came to the conclusion that when exercising the authority to approve the decision of the investigator to stop the investigation (Part 4 of Article 280 of the Criminal Code of Ukraine), the prosecutor must: 1) establish the fact of notification of the previously notified suspicion to a person in this criminal proceeding; 2) to establish the presence of one of the facts - grounds for stopping the investigation, defined in Part 1 of Article 280 of the Criminal Procedure Code of Ukraine and 3) check whether all unnecessary and possible procedural actions were carried out by the inquirer in this criminal proceeding before the decision to stop it was made. It was determined that the legal consequences of the prosecutor's cancellation of the decision of the investigator to stop the investigation are similar to the situations when such decisions are canceled by the investigating judge on the complaint of the defense party, the victim or the representative of a legal entity: the period of investigation from the day of the decision to stop the investigation to the day of its cancellation by the prosecutor is included in terms of pre-trial investigation.
Keywords: criminal proceedings; inquiry; public prosecutor; functions; authority; stopping the inquiry